Полынный свет: лирика / Евгений Карасев - Карасев Евгений Александрович (Молодая гвардия, 1988)
Экземпляры: КХ (20111102) / Инвентарный номер: 919776 / Цена: 0.25 / Сис.шифр: Р2 / Авт.знак: К 21 / ГРНТИ: 17 / ББК: 84(2)